2017
DOI: 10.1111/micc.12384
|View full text |Cite
|
Sign up to set email alerts
|

Muscle microcirculation alterations and relation to dipping status in newly diagnosed untreated patients with arterial hypertension—A pilot study

Abstract: The study suggests an impaired muscle microcirculation in newly diagnosed, untreated AH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In several tissues, capillary density was shown to be inversely correlated with blood pressure [28]. Furthermore, capillary rarefaction in skeletal muscle is associated with the elevation of arterial pressure in hypertensive individuals [29], and individuals with hypertension are often accompanied by skeletal muscle capillary rarefaction [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several tissues, capillary density was shown to be inversely correlated with blood pressure [28]. Furthermore, capillary rarefaction in skeletal muscle is associated with the elevation of arterial pressure in hypertensive individuals [29], and individuals with hypertension are often accompanied by skeletal muscle capillary rarefaction [15].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate skeletal muscle capillarization is not only beneficial to reduce peripheral resistance but also can provide enough amino acids and growth factors for skeletal muscle, thus promoting protein synthesis and muscle hypertrophy [13,14]. Individuals with hypertension often exhibit microcirculation impairment [15]. Accumulating evidence showed that exercise, no matter resistance exercise or endurance exercise, could increase skeletal muscle capillarization [16] and improve muscle hypertrophy [17,18].…”
Section: Introductionmentioning
confidence: 99%